VARIABILITY IN RECURRENT BEHAVIORS ELICITED BY PEOPLE WITH OBSESSIVE-COMPULSIVE DISORDER - Meera Robinson (International Journal of Multidisciplinary Research and Studies, 2021)
The lifetime prevalence of obsessive-compulsive disorder (OCD) ranges between 1% and 4%. 1,2 and demonstrates a considerable amount of diversity in terms of the clinical presentation and comorbidity profile. It has a chronic, unpredictable course that has a substantial impact on individuals and places a strain on carers. The average age at which OCD symptoms appear is bimodal, with the first peak occurring around the age of 11 and the second peak occurring in early adulthood. By the age of around twenty percent of all afflicted individuals had shown symptoms. 5 Obsessive-compulsive isorder that begins in childhood has attracted a lot of attention as an unique phenotype of OCD, having both genetic and developmental foundations. 6 Compulsions including cleaning, checking, ordering, and repeating are typical manifestations of OCD in children. Other common obsessions include contamination, aggression, symmetry, hoarding, and somatic symptoms.